Free gingival graft in the treatment of class III gingival recession - Remya V; Kishore Kumar K; Sudharsan Sabitha; Arun K (Wolters Kluwer Medknow Publications, 2008)
Aim: The purpose of this study was to assess the success and predictability of root coverage and esthetics obtained with free gingival grafts (FGGs) in the treatment of early class III gingival recessions for a period of 12 months. Materials and Methods: Ten patients contributed to 12 sites, each with early class III recession with interdental bone loss £4 mm from cemento enamel junction(CEJ). Clinical parameters recorded at baseline and at 1, 6, and 12 months were probing depth (PD), recession depth (RD), recession width (RW), and clinical attachment level (CAL). Results: Reduction of recession resulted in a significant gain in CAL and PD at the end of 12 months. A statistically significant mean root coverage of 41.25 ± 21.07% was obtained at the end of 12 months. A statistically significant improvement in Visual Analog Scale score was seen after a 12-month follow-up period. Conclusion: In a south Indian population, early class III gingival recessions treated with FGG procedures resulted in 40-50% root coverage with fairly acceptable esthetics.